Skeletal muscle delimited myopathy and verapamil toxicity in SUR2 mutant mouse models of AIMS - Conor McClenaghan; Maya A Mukadam; Jacob Roeglin; Robert C Tryon; Manfred Grabner; Anamika Dayal; Gretchen A Meyer; Colin G Nichols (EMBO Molecular Medicine)
Abstract ABCC9‐related intellectual disability and myopathy syndrome (AIMS) arises from loss‐of‐function (LoF) mutations in the ABCC9 gene, which encodes the SUR2 subunit of ATP‐sensitive potassium (KATP) channels. KATP channels are found throughout the cardiovascular system and skeletal muscle and couple cellular metabolism to excitability. AIMS individuals show fatigability, muscle spasms, and cardiac dysfunction. We found reduced exercise performance in mouse models of AIMS harboring premature stop codons in ABCC9. Given the roles of KATP channels in all muscles, we sought to determine how myopathy arises using tissue‐selective suppression of KATP and found that LoF in skeletal muscle, specifically, underlies myopathy. In isolated muscle, SUR2 LoF results in abnormal generation of unstimulated forces, potentially explaining painful spasms in AIMS. We sought to determine whether excessive Ca2+ influx through CaV1.1 channels was responsible for myopathology but found that the Ca2+ channel blocker verapamil unexpectedly resulted in premature death of AIMS mice and that rendering CaV1.1 channels nonpermeable by mutation failed to reverse pathology; results which caution against the use of calcium channel blockers in AIMS.